Identification of material properties of composite plates using Fourier-generated frequency response functions - Tam, Jun Hui; Ong, Zhi Chao; Lau, Chun Lek; Ismail, Zubaidah; Ang, Bee Chin; Khoo, Shin Yee (Taylor & Francis, 2019)
The present research adopts the use of Fourier-based plate model to synthesize FRFs for its proven prominent accuracy and incorporates with a hybrid optimization algorithm. The effectiveness of FRF error function in material identification consists in the trade-off range between those of natural frequency error function and mode shape error function with about 7% reduction in absolute relative error of the evaluated elastic moduli and shear modulus with respect to those of mode shape error function as well as approximately 25% reduction in absolute relative error of the identified Poisson's ratio with respect to that of natural frequency error function. © 2017, © 2017 Taylor & Francis Group, LLC.